APHORISM AS A PAREMIOLOGICAL UNIT - Begimqulova Marhabo Ismatulla qizi (Scholars Digest Publishing, 2023)
This article deal with study aphorisms as paremiological units. The issue of aphorisms in linguistics has been discussed.
Keywords: aphorism, philosophy, paremiography, paremias, paremiological unit.